154k views
2 votes
Explain what is happening at this step in the solving equation process.

1. 10 − 6 x = 4 + 5 x

2. 7-6x=1+5x

1 Answer

6 votes

Answer:

1. After solving we get value of x:
\mathbf{x=(6)/(11) }

2. After solving we get value of x:
\mathbf{x=(6)/(11) }

Explanation:

We need to Solve the equations.

1.
10 - 6 x = 4 + 5 x

Step 1: Subtract 5x on both sides


10 - 6 x-5x = 4 + 5 x-5x\\10-11x=4

Step 2: Subtract 10 on both sides


10-11x-10=4-10\\-11x=-6

Step 3: Divide both sides by -11


(-11x)/(-11)=(-6)/(-11)\\x=(6)/(11)

So, after solving we get value of x:
\mathbf{x=(6)/(11) }

2.
7-6x=1+5x

Step 1: Subtract 5x on both sides


7 - 6 x-5x = 1 + 5 x-5x\\7-11x=1

Step 2: Subtract 7 on both sides


7-11x-7=1-7\\-11x=-6

Step 3: Divide both sides by -11


(-11x)/(-11)=(-6)/(-11)\\x=(6)/(11)

So, after solving we get value of x:
\mathbf{x=(6)/(11) }

User Murven
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.